2021
DOI: 10.1590/1982-0224-2021-0056
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of euchromatic B chromosomes in natural populations of Moenkhausia bonita and M. forestii (Pisces: Characidae)

Abstract: Moenkhausia is a highly specious genus among the Characidae, composed of 96 valid species. Only twelve species have a known karyotype. Thus, here are presented the first cytogenetic data of two allopatric populations of Moenkhausia bonita and one of M. forestii, both belonging to the upper Paraná River basin (PR) with discussion on the evolutionary and cytotaxonomic aspects of the genus. The two species presented 2n = 50 chromosomes but different karyotype formulas and occurrence of 1-2 B chromosomes. These el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Bs have shown a great intra- and inter-specific diversity in the proportion of euchromatic and heterochromatic regions. Ranucci et al (2021) showed that Bs in two species of fish, Moenkhausia bonita and its allopatric species M. forestii , vary in the relative position as well as the content of the heterochromatin. In M. bonita , there is little heterochomatin found at the terminal and peri-centromeric regions and in M. forestii , on the other hand, extensive heterochromatic blocks are present in the interstitial regions.…”
Section: Structural Organization and Composition Of Bsmentioning
confidence: 99%
“…Bs have shown a great intra- and inter-specific diversity in the proportion of euchromatic and heterochromatic regions. Ranucci et al (2021) showed that Bs in two species of fish, Moenkhausia bonita and its allopatric species M. forestii , vary in the relative position as well as the content of the heterochromatin. In M. bonita , there is little heterochomatin found at the terminal and peri-centromeric regions and in M. forestii , on the other hand, extensive heterochromatic blocks are present in the interstitial regions.…”
Section: Structural Organization and Composition Of Bsmentioning
confidence: 99%